MACERAL AND MINERAL ANALYSIS OF LEBAK COALS REGARDING THEIR UTILISATION - BINARKO SANTOSO; BUKIN DAULAY (Puslitbang tekMIRA, 2007)
Type and rank variations of Lebak coals were derived from twenty-eight samples of Palaeogene coalfield (Bayah, Cimandiri and Cihideung) and Neogene coalfields (Bojongmanik) using petrographic analy- ses. The Lebak coals are dominated by vitrinite, liptinite and minor inertinite and mineral matter as well. The coal type, in terms of maceral and mineral compositions, reflects climatic influences and differences in peat conditions. Higher vitrinite reflectance of Palaeogene coals, compared to Neogene ones, is a result of higher regional coalification level in the basin, associated with greater cover and local effect of igneous intrusion. The Palaeogene coals have better quality than the Neogenes and is also supported by higher specific energy. The coals that are vitrinite-rich, liptinite and inertinite-poor are suitable for direct combustion.